To the problem of prolongation of operational life of power equipment: Fìz.-mat. model. ìnf. tehnol. 2018, 27:62-69 - Drobenko, Bohdan; Budz, Stepan; Astashkin, Volodymyr (PHYSICO-MATHEMATICAL MODELLING AND INFORMATIONAL TECHNOLOGIES, 2019)
The approach to the determination of the stress-strain state of the power equipment elements and the investigation of the possibility of their further operation is considered. It is based on the determination of the 3D temperature distributions and displacement fields, deformations and stresses from the complete system of equations of non-isothermal thermo-elastic-plasticity. The state of the operating drum of the steam boiler was studied taking into account existing defects, repair procedures and material degradation using the software developed on the basis of the finite element method. Recommendations for improvement of the technology for its repair have been developed and conditions and terms for its safe further exploitation have been established. References Drobenko, B.D., Budz, S.F., Astashkin, V.I. (2014). Otsinka prydatnosti elementiv enerhetychnoho obladnannia do ekspluatatsii ponad parkovyi resurs. Nauka ta innovatsii, 10(1), 5-16. https://doi.org/10.15407/scin10.05.005 PNAE G-7-002-87. (1989). Normyi rascheta na prochnost oborudovaniya i truboprovodov atomnyih energeticheskih ustanovok. M. Energoatomizdat. (1987). Kotlyi statsionarnyie i truboprovodyi para i goryachey vodyi. Normyi rascheta na prochnost OST 108.031.08-85 — OST 108.031.10-85. M.: Izd. Ministerstva energeticheskogo mashinostroeniya. (2009). Instruktsiia SOU 40.1-21677681-02:2009. Poriadok prodovzhennia terminu ekspluatatsii barabaniv kotliv vysokoho tysku. K.: Obiednannia enerhetychnykh pidpryiemstv «Haluzevyi rezervno-investytsiinyi fond rozvytku enerhetyky». Lyberman, L. Ia., Peisykhis, M.Y. (1966). Svoystva staley i splavov, primenyaemyih v kotlo-turbostroenii. Rukovodiashchye ukazanyia, 16(1), 220 p. Budz, S.F., Drobenko, B.D., Mykhailyshyn, V.S. (1992). Kompyuternoe modelirovanie termouprugoplasticheskogo povedeniya mehanicheskih sistem. IPPMM AN USSR. Hachkevych, O. R., Drobenko, B. D. (2004). Matematychne modeliuvannia induktsiinoho nahrivu elektroprovidnykh til. Visnyk Lvivskoho universytetu. Ser. prykl. mat. ta inform, 8, 97-111 Drobenko, B., Hachkevych, O. & Hetnarski, B. (Ed.) (2014). Thermomechanics of electroconductive solids. Springer Dordrecht, Heidelberg, New York, 11, 6052-6063. https://doi.org/10.1007/978-94-007-2739-7_627 Hachkevych, O. R., Drobenko, B. D. & Burak, Ya .I., Kushnir, R. M. (Ed.). (2010). Modeliuvannia ta optymizatsiia v termomekhanitsi elektroprovidnykh neodnoridnykh til: Termomekhanika namahnechuvanykh elektroprovidnykh termochutlyvykh til (Vol. 4). Lviv: SPOLOM. Hachkevych, O.R., Drobenko, B.D. (2007). Osoblyvosti chyslovoho rozviazuvannia zviazanykh zadach pro vyznachennia elektromahnitnykh, teplovykh i mekhanichnykh poliv u deformivnykh termochutlyvykh elektroprovidnykh tilakh za kvaziustalenykh elektromahnitnykh navantazhen. Mat. metody ta fiz.-mekh. polia, 50(3), 166-177. https://doi.org/10.1016/j.ijheatmasstransfer.2006.07.013 Drobenko, B.D. (2012). Computational experiment for determination of the cyclic durability of a boiler drum of a thermal power plant. Materials Science, 48(1), 76-82. https://doi.org/10.1007/s11003-012-9474-1 Hachkevych, O. Drobenko, B. (2003). Matematychne modeliuvannia termomekhanichnykh protsesiv v osesymetrychnykh elektroprovidnykh tilakh za elektromahnitnykh navantazhen. Mashynoznavstvo, 4(70), 3-7.